Revolutionizing nitrogen fixation: communicating the potentials of nanostructured photocatalysts for sustainable ammonia/nitrate synthesis - Sharhabil Musa Yahaya; Nafiu Abdu; Ibrahim Abubakar Aliyu; Bello Mukhtar (Circular Agricultural Systems)
Photocatalytic nitrogen fixation (PNF) using nanostructured materials is a promising approach that is likely to rival the most expensive and high-energy-demanding Harber-Bosch method of ammonia synthesis. This is because the process is deemed the most sustainable method of nitrogen fixation, through the direct production of ammonia and/or nitrate from water and atmospheric nitrogen with the aid of sunlight; and the system has zero emission of carbon dioxide. The PNF process is receiving much attention making it among the hot research topics in recent years. There is, however, a knowledge gap between the photocatalytic processes and the nanostructured photocatalyst. In this review, therefore, recent breakthroughs and achievements in the photocatalytic reaction processes were discussed. In addition, the nanostructured photocatalysts used in nitrogen fixation were discussed in detail. This includes the importance of the nanomaterials in photocatalysis, the types used in photocatalytic nitrogen fixation, and the synthesis methods of the nanomaterials. Also, limitations that affect the photocatalytic reaction processes as well as the ways of overcoming them such as the creation of oxygen, sulphur, and nitrogen vacancies, doping techniques, formation of heterojunctions, and the use of cocatalysts were all discussed in detail. From the aforementioned discussions, PNF could be seen as the most eco-friendly and sustainable method of nitrogen fixation. However, understanding the mechanisms of PNF is very critical to identifying and designing an efficient photocatalytic system.